THE APPLICATION OF RELIGIOUS MODERATION CONCEPT IN INDONESIAN LANGUAGE TEACHING: A CASE STUDY IN ISLAMIC SCHOOLS AND ISLAMIC UNIVERSITIES (PERGURUAN TINGGI KEAGAMAAN ISLAM/PTKI) - Siti Isnaniah; Islahuddin Islahuddin (Balai Penelitian dan Pengembangan Agama Jakarta, 2022)
Indonesia consists of various ethnic groups, religions, races, groups so that it can cause conflict if it is not anticipated properly. Therefore, the concept of religious moderation needs to be applied in various fields, one of which is in the field of education. This study aims to explain qualitatively the application of the concept of religious moderation in Indonesian language learning in Islamic schools and university's tri dharma activities including Lectures on Indonesian Language Courses in the Indonesian Tadris Study Program(Tadris Bahasa Indonesia/TBI) UIN Raden Mas Said Surakarta. The data sources are documents, informants, and events. Data collection techniques used content/document analysis, interviews, and observations. The data validity technique uses triangulation. The data analysis technique uses an interactive model. The results of the research are shown by the application of the concept of religious moderation through the university's tri dharma, namely education, research, and community service. In the field of education, it can be started with the TBI Study Program curriculum which incorporates the values of moderation in each subject, this can be seen in the RPS, as well as student activities with the theme of religious moderation; In addition, there is a compulsory faculty subject, namely the Constitutional Court of Religious Moderation Insights. In the field of research, there are no published scientific, technological or research papers from lecturers or students, all of which are still in the process of being published. In the field of PkM, Continuing Professional Development (PKB) training was conducted for Indonesian language teachers in Sumatra and Java. This activity is a work program of the Ministry of Religion's REP-MEQR, in collaboration with the World Bank. The conclusion of this research is that the TBI Study Program is considered successful in applying the concept of religious moderation in the field of education and PkM, for research needs to be improved again.